2009 IEEE International Frequency Control Symposium Joint With the 22nd European Frequency and Time Forum 2009
DOI: 10.1109/freq.2009.5168149
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of surface acoustic wave wireless pressure sensor

Abstract: This paper deals with walk-through allowing to explain the electrical response of a surface acoustic wave (SAW) resonator under inhomogeneous stress. Act of pressure on a circular membrane where is put the resonator induces inhomogeneous stress and changes the resonance frequency and the quality factor of the resonator. This paper describes a developped model based on P-matrix approach allowing to explain the behavior of these two parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…1 lists the pressure sensitivities of SAW pressure sensors reported in some typical works. It can be found that the sensitivity in this work is higher than that reported in [3][4][5][6] and [13,14]. Then it is interesting to investigate the reasons for the high pressure sensitivity of our SAW pressure sensor.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…1 lists the pressure sensitivities of SAW pressure sensors reported in some typical works. It can be found that the sensitivity in this work is higher than that reported in [3][4][5][6] and [13,14]. Then it is interesting to investigate the reasons for the high pressure sensitivity of our SAW pressure sensor.…”
Section: Resultsmentioning
confidence: 60%
“…On the other hand, the SAW pressure sensors reported in [3][4][5][6] and [13,14] are diaphragm-type SAW pressure sensors, which means that the SAW resonator was fabricated or pasted on the diaphragm. According to Sinha's research [8], the pressure subjected to the diaphragm could be regarded as biaxial stress (strain).…”
Section: Resultsmentioning
confidence: 99%
“…The identification of the resonance frequency allows for recovering the physical quantity under investigation via conversion coefficients and physical relations. A parabolic frequency-temperature law is generally used to derive the temperature to which the sensor is submitted [17], whereas linear relations are used for determining torque [18] or pressure [19] via SAW stress sensitivity coefficients. Assuming a properly designed transducer, our investigation focuses on the packaging of the sensor to be operated in a high temperature environment.…”
Section: Surface Acoustic Wave Interrogation Principlementioning
confidence: 99%
“…Parallèlement au développement du capteur à 2,45 GHz, un capteur à 434 MHz utilisant un résonateur à ondes de Rayleigh a donc été conçu et fabriqué [6]. Une tranche de quartz sur laquelle on a au préalable réalisé un résonateur est scellée sur une tranche de silicium usiné.…”
Section: Résultats De Mesure à L'aide D'un Capteur De Pression à 434 unclassified